Populism as an intra-party phenomenon: The British Labour Party under Jeremy Corbyn. (February 2019) - Watts, Jake; Bale, Tim
This article seeks to demonstrate that the concept of populism can help us to understand the dynamics of intra -party politics. This argument is made via a case study of the British Labour Party under Jeremy Corbyn, who was elected as its leader in late 2015. Corbynism as a (highly personalistic) political phenomenon has relied, in its resistance to opposition from more moderate MPs to Labour's leftward turn, upon the idea that the party's members are 'the people'. This idea links to notions of the 'heartland' members occupy, the elite conspiracy against them and the democratic resolution made possible by the leader. Analysing how the rise of populist politics affects politics within parties, as well as between them, may, the article argues, help account for the populist transformation of established parties. This transformation, in turn, is one way in which populist discourse may infuse a country's politics, permanently or otherwise.